150 YEARS OF BOOM AND BUST: WHAT DRIVES MINERAL COMMODITY PRICES?. (9th September 2016) - Stuermer, Martin
Abstract : This paper provides long-run evidence on the dynamic effects of supply and demand shocks on commodity prices. I assemble and analyze a new data set of price and production levels of copper, lead, tin, and zinc from 1840 to 2014. Using a novel approach to identification, I show that price fluctuations are primarily driven by demand, rather than supply shocks. Demand shocks affect the price for up to 15 years, whereas the effect of mineral supply shocks persists for up to 5 years. Price surges caused by rapid industrialization are a recurrent phenomenon throughout history. Mineral commodity prices return to their declining or stable trends in the long run.